IMPLEMENTASI PEMBUATAN DAN PEMASARAN PRODUK HIC (HEALTHY ICE CREAM) BERBASIS SAYUR DARI WORTEL DI SEMARANG BARAT - Dwi Retnaningsih; Muhammad Azkanni’am; Aulia Dewi Hastuti; Nurul Mufidah (Universitas Pahlawan Tuanku Tambusai, 2022)
Ice cream is a kind of semi-solid food made from a mixture of milk, animal or vegetable fat, sugar and or without other food ingredients. Ice cream is one of the foods with high nutritional value. The nutritional value of ice cream is highly dependent on the nutritional value of the raw material. The implementation of the program for making Healthy Ice Cream based on vegetables from carrots to maintain eye health from free radicals consists of three stages, namely: Production, ice cream production, and ice cream marketing. The plan to make vegetable ice cream from carrots is to look at the situation in the surrounding environment, especially for students and schoolchildren who are increasingly attached to gadgets during the pandemic. Therefore, we are innovative in making food that is of interest to all circles, especially school children and students which contains vitamin A which can nourish the eyes, namely carrot ice cream. The existence of HIC (Healthy Ice Cream) based on carrots from carrots in the West Semarang area can more or less help students or schoolchildren in meeting the needs of vitamin A to maintain eye health by consuming this vegetable ice cream from carrots. In addition to a cheap and affordable price, this ice cream can eliminate thirst and can be refreshing when first touched on the tongue.